Layout optimization for multi-bi-modulus materials system under multiple load cases. (October 2016) - Shi, Jiao; Cao, Jing; Cai, Kun; Wang, Zhenzhong; Qin, Qing-Hua
Abstract An optimization model is presented for obtaining optimal layout of multiple bi-modulus materials systems under multiple load cases (MLC). In the optimization model, the objective function is the linearly weighted structural compliance under MLC. The bi-modulus materials in a finite element are replaced by isotropic materials according to the stress state of that element. The equivalent mechanical properties of an element are expressed as the power–law function of the volume fractions (design variables) and moduli of the solid phases. Numerical experiments are presented to verify the validity and efficiency of the present algorithm. The effects of factors including the bi-modulus behavior of materials, the load directions and the weighting schemes of MLC are also investigated numerically.